Pengaruh Perputaran Kas dan Perputaran Persediaan terhadap Profitabilitas Perusahaan Sub Sektor Advertising Printing Media yang Terdaftar di Bursa Efek Indonesia - Ainia Rahmawati; Susanti Susanti (Prodi Akuntansi Fakultas Ekonomi Universitas Hasyim Asy'ari, 2020)
The purpose of this research was to know the influence of cash turnover and inventory turnover on the profitability of the advertising printing media sub-sector companies registered in Indonesia Stock Exchange. This study used quantitative methods. There were two independent variables: cash turnover (X1) and inventory turnover (X2) in this research, and the dependent variable is profitability (Y). The instrument used in this research is secondary data with engineering data retrieval form of documentation of the financial statements. The result showed that cash turnover had an impact on profitability. However, the effect of this variable was negative. This negative effect could be interpreted that an increase in cash turnover would precisely be followed by the profitability decrease. On the other hand, inventory turnover had no influence on profitability. But, both cash turnover and inventory turnover simultaneously influenced the profitability.